Belajar bahasa arab dengan bernyanyi / Barokatussolihah; editor, H. Jauhar Mustofa; penerbit, Safira Insani Press. - BAROKATUSSOLIHAH; Jauhar Musthofa, H (Safira Insani Press, 2013)
130 hlm. : ilus. ; 24 cm.